Water balance of Maninjau watershed with SWAT hydrological model. Issue 1 (July 2020) - Ridwansyah, I; Rustini, H A; Yulianti, M; Apip,; Harsono, E
Abstract: Lake Maninjau was one of the international tourist destinations before the 2000s. Aside from being used as a source of 66 MW hydroelectric power built in 1972, currently, this caldera lake is also used for aquaculture. Lake Maninjau ecosystem, which consists of water bodies and watersheds, has an area of 23, 729.3 Ha. The surface area of Lake Maninjau at +461.5 m asl is 9, 737.5 Ha. Calculation of water balance in the Lake Maninjau watershed becomes a necessity because of its multi-functional status. Maninjau watershed water balance is estimated using SWAT (Soil and Water Assessment Tools) model. Rainfall data from Climate Hazard Group InfraRed Precipitation with Station (CHIRPS) was reanalyzed and compared with local rainfall data. The simulation conducted for 1981 - 2019 on the sub-watershed scale produced NSE and R 2 values of 0.61 and 0.7, respectively. The simulation was scaled up for the entire catchment of Lake Maninjau. Simulation results showed that an average annual rainfall of 2, 483.9 mm/year produced a surface flow, interflow, base flow, and recharge to aquifer of 7.8 mm/year, 1397.4 mm/year, 273.4 mm/year and 14.7 mm/year, respectively.